Synergistic Antibiofilm Effects of Pseudolaric Acid A Combined with Fluconazole against Candida albicans via Inhibition of Adhesion and Yeast-To-Hypha Transition - Bin Zhu (Microbiology Spectrum, 2022)
ABSTRACT Candida albicans biofilms are resistant to several clinical antifungal agents. Thus, it is necessary to develop new antibiofilm intervention measures. Pseudolaric acid A (PAA), a diterpenoid mainly derived from the pine bark of Pseudolarix kaempferi, has been reported to have an inhibitory effect on C. albicans. The primary aim of the current study was to investigate the antibiofilm effect of PAA when combined with fluconazole (FLC) and explore the underlying mechanisms. Biofilm activity was assessed by tetrazolium {XTT [2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide salt]} reduction assays. PAA (4 μg/mL) combined with FLC (0.5 μg/mL) significantly inhibited early, developmental, and mature biofilm formation compared with the effect of PAA or FLC alone (P < 0.05). Furthermore, PAA (4 μg/mL) combined with FLC (0.5 μg/mL) produced a 56% reduction in C. albicans biofilm adhesion. The combination of PAA (4 μg/mL) and FLC (0.5 μg/mL) also performed well in inhibiting yeast-to-hypha transition. Transcriptome analysis using RNA sequencing and quantitative reverse transcription PCR indicated that the PAA-FLC combination treatment produced a strong synergistic inhibitory effect on the expression of genes involved in adhesion (ALS1, ALS4, and ALS2) and yeast-to-hypha transition (ECE1, PRA1, and TEC1). Notably, PAA, rather than FLC, may have a primary role in suppressing the expression of ALS1. In conclusion, these findings demonstrate, for the first time, that the combination of PAA and FLC has an improved antibiofilm effect against the formation of C. albicans biofilms by inhibiting adhesion and yeast-to-hypha transition; this may provide a novel therapeutic strategy for treating C. albicans biofilm-associated infection. IMPORTANCE Biofilms are the primary cause of antibiotic-resistant candida infections associated with medical implants and devices worldwide. Treating biofilm-associated infections is a challenge for clinicians because these infections are intractable and persistent. Candida albicans readily forms extensive biofilms on the surface of medical implants and mucosa. In this study, we demonstrated, for the first time, an inhibitory effect of pseudolaric acid A alone and in combination with fluconazole on C. albicans biofilms. Moreover, pseudolaric acid A in combination with fluconazole exerted an antibiofilm effect through multiple pathways, including inhibition of yeast-to-hypha transition and adhesion. This research not only provides new insights into the synergistic mechanisms of antifungal drug combinations but also brings new possibilities for addressing C. albicans drug resistance.